2012
DOI: 10.1016/j.joca.2012.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium oscillations in articular chondrocytes induced by basic calcium phosphate crystals lead to cartilage degradation

Abstract: BCP crystals can induce variation in iCa(2+) content and oscillations in articular chondrocytes. Furthermore, BCP crystal-induced changes in iCa(2+) content play a pivotal role in BCP catabolic effects on articular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 38 publications
0
13
0
2
Order By: Relevance
“…Several experimental data supported that intracellular Ca(2+) variations could mediate catabolic responses in OA chondrocytes [16,17]. In the adjuvant-induced arthritis rat model, treatment with amiloride, a voltage-gated Ca(2+) channel blocker, significantly decreased Mankin scores, while increased Col II and AGG mRNA and protein expression and reduced articular cartilage destruction [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental data supported that intracellular Ca(2+) variations could mediate catabolic responses in OA chondrocytes [16,17]. In the adjuvant-induced arthritis rat model, treatment with amiloride, a voltage-gated Ca(2+) channel blocker, significantly decreased Mankin scores, while increased Col II and AGG mRNA and protein expression and reduced articular cartilage destruction [16].…”
Section: Discussionmentioning
confidence: 99%
“…In the adjuvant-induced arthritis rat model, treatment with amiloride, a voltage-gated Ca(2+) channel blocker, significantly decreased Mankin scores, while increased Col II and AGG mRNA and protein expression and reduced articular cartilage destruction [16]. More recently, it has been shown that intracellular calcium oscillations in articular chondrocytes induced by basic calcium phosphate crystals led to cartilage degradation [17]. This can be combined with our data that the PLC-γ1/IP3/Ca(2+)/CaMK II axis is more dominant than the PLC-γ1/DAG/PKC axis in PLC-γ1-dependent ECM synthesis of human OA chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ oscillations have been reported in a great variety of non-excitable cells including pancreatic β-cells [49], embryonic stem cells (ESCs) [47], chondroblasts [11,35], chondrocytes [40] and human MSCs [22,24]. This is the first study to report that human chondroprogenitor cells derived from regions with minor lesions of osteoarthritic articular cartilage (CPCs) are also characterised by a similarly dynamic Ca 2+ homeostasis.…”
Section: Dynamics Of Cytosolic [Ca 2+ ]Imentioning
confidence: 96%
“…Indeed, NMDA-receptors with altered subunit composition and activity were described in OA chondrocytes [44]; furthermore, intracellular calcium oscillations associated with inorganic calcium crystal-induced cartilage matrix degradation were also observed [40]. These alterations can serve as a background for modified metabolism and altered physiological properties of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, bovine articular chondrocytes within cartilage explants, when exposed to basic calcium phosphate crystals, had significant increases in intracellular calcium content, which is correlated with cartilage matrix degradation [80]. Another ECM component that affects chondrocyte metabolism is fibronectin, which showed a significant positive correlation between chondrocyte apoptosis and fibronectin content [81].…”
Section: The Effects Of Changes In Extracellular Matrix On Articulmentioning
confidence: 99%